(untitled) (Theatrum historiae, 2013)
The text explores historical development of Scottish national identity. The issue is analysed from different angles which basically reflect different types of individual identities. The development of Scottishness is first assessed in terms of Anglo-Scottish relations, using the dual perspective of coloniser/colonised. The following phenomena reflect Scottish regional identity and the historical development of regional relationships, social identity and the historical development of gender representation within the notion of Scottishness.